Posterior urethral valves and vesicoureteral reflux: can prenatal ultrasonography distinguish between these two conditions in male fetuses?. (29th July 2016) - Chitrit, Yvon; Bourdon, Mathilde; Korb, Diane; Grapin‐Dagorno, Christine; Joinau‐Zoulovits, Félicia; Vuillard, Edith; Paye‐Jaouen, Annabel; Peycelon, Matthieu; Belarbi, Nadia; Delezoide, Anne‐Lyse; Schmitz, Thomas; El Ghoneimi, Alaa; et al.
Abstract: Objective: The objective of the study was to evaluate prenatal sonographic signs that distinguish male fetuses with posterior urethral valves (PUV) from those with vesicoureteral reflux (VUR). Methods: Prenatal data were retrospectively retrieved from all consecutive women delivering between 2003 and 2012 of a male newborn with a postnatal diagnosis of PUV or VUR. Prenatal parameters included fetal bladder characteristics, identification of a dilated posterior urethra, and change in shape and size in the fetal renal pelvis or ureter. Results: One hundred thirty‐six women gave birth to a male newborn with a postnatal diagnosis of PUV ( n  = 49) or VUR ( n  = 87). The presence of posterior urethral dilatation [21 (42.9%) fetuses versus 0 (0%), p  = 0.000], a thickened fetal bladder wall [37 (75.5%) vs 4 (4.6%), p  = 0.000], and anhydramnios [14 (28.6%) vs 0, p  = 0.000] were strongly associated with the postnatal diagnosis of PUV. Change in shape and size in the fetal renal pelvis or ureter was observed in 15 (17.2%) of 87 children with VUR versus 1 (2.0%) out of 49 with PUV ( p  = 0.010). Conclusions: Prenatal ultrasound may differentiate with reasonable accuracy male fetuses with a postnatal diagnosis of PUV from those with VUR. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Thick‐walled bladder, dilated bladder, and oligoanhydramnios are associated with posterior urethral valves (PUV). The relavance of the keyhole sign is less clear. What Does This Study Add? This is a large cohort study with as purpose defining ultrasound variables that point to either PUV or vesico‐ureteral reflux (VUR). A thick bladder wall and anhydramnios are associated with the postnatal diagnosis of PUV. Posterior urethral dilatation seems pathognomonic for PUV.